Teachers Attitudes towards Certain Aspects of Managing Educational Change in Lithuania - Želvys, Rimantas (Acta Paedagogica Vilnensia, 1998)
A survey has been conducted of teachers attitudes towards managing educational change in Lithuania. 117 responses to an opinion questionnaire were received. The survey was intended to examine teachers attitudes towards education policy of the country, evaluation of the ongoing educational reform, position towards power distribution between the Ministry of Education and Science, local educational authorities, and headteachers. The survey also explored attitudes towards teacher training and appraisal. Findings indicate that teacher attitudes towards educational reform and devolution of power are mostly neutral. Strictly negative attitude was .expressed towards the way the Parliament and the Government are solving educational problems. A strong beliet that society and non-governmental organisations should play bigger role in Lithuanian education was expressed.
Keywords: educational management; educational change; teacher; teacher training; appraisal